2003
DOI: 10.1093/jat/27.4.253
|View full text |Cite
|
Sign up to set email alerts
|

Three Fatal Cases of PMA and PMMA Poisoning in Denmark

Abstract: Paramethoxyamphetamine (PMA) and paramethoxymetamphetamine (PMMA) are methoxylated phenylethylamine derivatives with effects similar to methylenedioxymetamphetamine (MDMA) and sold as such. However, PMA and PMMA are more potent than MDMA, but have a slower onset of action, which encourages users to take more. Three fatal cases involving PMA and PMMA in Denmark in year 2000 are investigated including history, pathological, and toxicological findings. The methods used for extraction, identification, and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…However, most studies on subjective effects of BZP were done in healthy, drug-naive volunteers and doses were not determined in the present study, important factors which might contribute to the differences in effects found and make comparisons difficult. The adverse subjective effects reported in this study after ingestion of tablets containing MDMA with PMMA largely support the existing toxicological findings by others of casualties and fatalities after consumption of PMMA or its metabolite PMA (Caldicott et al 2003;Johansen et al 2003;Becker et al 2003;Lin et al 2007). Extreme hyperthermia was described as one of the symptoms of PMMA intoxication, especially in crowded environments (Rohanova and Balikova 2009;Páleníček et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…However, most studies on subjective effects of BZP were done in healthy, drug-naive volunteers and doses were not determined in the present study, important factors which might contribute to the differences in effects found and make comparisons difficult. The adverse subjective effects reported in this study after ingestion of tablets containing MDMA with PMMA largely support the existing toxicological findings by others of casualties and fatalities after consumption of PMMA or its metabolite PMA (Caldicott et al 2003;Johansen et al 2003;Becker et al 2003;Lin et al 2007). Extreme hyperthermia was described as one of the symptoms of PMMA intoxication, especially in crowded environments (Rohanova and Balikova 2009;Páleníček et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Designer drugs are a serious problem worldwide, especially among young people, and in some cases they have resulted in fatal poisoning [1][2][3][4][5][6][7]. New designer drugs are created by changing the molecular structure of an existing drug.…”
Section: Introductionmentioning
confidence: 99%
“…This creates a compound with similar pharmacological effects, and is performed to circumvent existing drug laws. For example, 4-methoxymethamphetamine (4-MMA) and 4-fluoromethamphetamine (4-FMA), which are 4-substituted psychoactive analogs of methamphetamine (MA), have emerged on the illicit drug market [1,2,[8][9][10][11]. Designer drugs such as illicit amphetamine-type stimulants are often co-administered with other drugs in tablet, capsule, or powder form [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, the abuse of their designer drugs including p-methoxyamphetamine (PMA) analogues and 2-methylamino-1-(3,4methy-lenedioxyphenyl)-propan-1-one (methylone) analogues, as shown in Fig. 1, have also been on the rise in Japan as well as in Europe and the U.S.A. [6][7][8][9][10][11][12] More recently, the Japanese authorities, therefore, have begun to prevent not only the recreational uses of the designer drugs under Narcotics and Psychotropics Control Law, but also the importation and distribution under Pharmaceutical Affairs Law.…”
Section: Introductionmentioning
confidence: 99%